2016
DOI: 10.1177/2168479016641719
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Health Care Practitioners’ Preferences for Medical Information: Collective Insights for Impacting Patient Care

Abstract: These findings provide information regarding the utility of medical information services while providing insights on the informational needs of health care professionals today. MI departments provide an important service to health care professionals that impart confidence for making treatment decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…2 Recently, Fung et al reported that up to 21% of customers (varying depending on Customer Group) even preferred receiving medical information by directly accessing a medical information website. This appears to be the case more so for pharmacists and nurses 10 than for physicians.…”
Section: Discussionmentioning
confidence: 95%
“…2 Recently, Fung et al reported that up to 21% of customers (varying depending on Customer Group) even preferred receiving medical information by directly accessing a medical information website. This appears to be the case more so for pharmacists and nurses 10 than for physicians.…”
Section: Discussionmentioning
confidence: 95%
“…3 However, Fung et al conducted a survey with US HCP where it was demonstrated that phone conversations continue to be a preference while alternate routes of communications such as mobile apps, video chats, or text are less favorable. 21 These studies suggest that mobile optimization, the use of smartphones and tablets for clinical information, will continue to grow while phone conversations also continue to be an important factor of medical communications. There are options for optimizing the user’s experience accessing MI on a mobile device.…”
Section: Discussionmentioning
confidence: 99%
“…While studies have reported that healthcare professionals and patients value the medical content provided by Med-Info departments measured by reported usage of information and/or action taken [7,8], there is still a lack of awareness among healthcare professionals (HCPs) and patients about pharmaceutical industry MedInfo services. Individual companies have been unsuccessful in addressing this knowledge gap and bringing visibility to the value of pharmaceutical industry MedInfo services [9,10].…”
Section: Recent Reports Describe Expanded Activities Highlighted In Tmentioning
confidence: 99%